2009
DOI: 10.1073/pnas.0813345106
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of PTC124 activity in cell-based luciferase assays of nonsense codon suppression

Abstract: High-throughput screening (HTS) assays used in drug discovery frequently use reporter enzymes such as firefly luciferase (FLuc) as indicators of target activity. An important caveat to consider, however, is that compounds can directly affect the reporter, leading to nonspecific but highly reproducible assay signal modulation. In rare cases, this activity appears counterintuitive; for example, some reporter gene assays ͉ high-throughput screening ͉ Ataluren

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
211
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(220 citation statements)
references
References 33 publications
(42 reference statements)
8
211
1
Order By: Relevance
“…S1C) (21). It has been suggested that ataluren is an inhibitor of firefly luciferase and that its reported nonsense suppression activity simply reflects stabilization of the luciferase enzyme (18,22). We consider this claim to be spurious because (i) ataluren-mediated readthrough has been observed in numerous other systems ( Fig.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…S1C) (21). It has been suggested that ataluren is an inhibitor of firefly luciferase and that its reported nonsense suppression activity simply reflects stabilization of the luciferase enzyme (18,22). We consider this claim to be spurious because (i) ataluren-mediated readthrough has been observed in numerous other systems ( Fig.…”
Section: Resultsmentioning
confidence: 67%
“…1). This result was attributable to readthrough of the reporter mRNA's premature UGA codon, and not protein stabilization (18), because ataluren treatment of 293H cells stably expressing WT NanoLuc had no effect on NanoLuc activity (Fig. 1B).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…From the primary screen, compounds that gave rise to a signal Ͼ2.2-fold (Ϸ5,000 compounds) over the plate averageassuming that most compounds are inactive and can serve as controls (31)-were selected for reanalysis in triplicate. Measurements with these putative hit compounds were collected and averaged, and those that activated the luciferase signal 2.5-fold over DMSO-treated controls (Ϸ1,000 compounds) were counterscreened in a cell-based SV40-driven firefly luciferase assay to rule out false-positives that directly and nonspecifically activate luciferase reporters (32). Compounds that reproducibly hit in the Nanog assay but did not hit in the SV40 assay were further analyzed in a dose-response format to identify the optimal concentration for activity ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…are employees or consultants of PTC Therapeutics, Inc. 1 To whom correspondence should be addressed. E-mail: speltz@ptcbio.com.…”
mentioning
confidence: 99%